Gender Discrimination of Women in Baseball Girl Movie: A Study of Semiotics - Amalia, Dina; Harahap, Rizky Daniaty; Prismayanti, Rini (International Journal Linguistics of Sumatra and Malay, 2022)
The representation of women by the entertainment media as well as in the real world is always described as very typical, one of them is that they can only carry out limited professions and activities. So that the existence of women is not represented proportionally. Based on this, the study aims to describe the signs of women's gender discrimination and equality. This study used the semiotic theory of Roland Barthes which describes the forms of denotative meaning, connotative meaning, and myths contained in the Baseball Girl movie. The method used in this research is descriptive qualitative with listening and note-taking techniques. The results found in the Baseball girl movie are as follows: (1) the meaning of denotation in this study described the gender discrimination of women who are considered weak by the coach or the professional baseball recruiting team in participating in the trials towards the professional baseball team. (2) The connotative meaning found in this film shows four forms of gender discrimination, namely marginalization, stereotype, subordination, and violence. (3) The myth that can be concluded in this study is that there is a culture that is believed by the coach, the professional baseball team recruiter, and the mother of the main female character in this film who considers women physically weaker than men.